2017
DOI: 10.1371/journal.pone.0184067
|View full text |Cite
|
Sign up to set email alerts
|

Identification of vaccine-derived rotavirus strains in children with acute gastroenteritis in Japan, 2012-2015

Abstract: Two live attenuated oral rotavirus vaccines, Rotarix and RotaTeq, have been introduced as voluntary vaccination in Japan since 2011 and 2012, respectively. Effectiveness of the vaccines has been confirmed, whereas concerns such as shedding of the vaccine strains and gastroenteritis cases caused by vaccine strains are not well assessed. We aimed to identify the vaccine strains in children with acute gastroenteritis (AGE) to investigate the prevalence of AGE caused by vaccination or horizontal transmission of va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 37 publications
0
14
1
Order By: Relevance
“…Two Rotarix ™ and RotaTeq ™ RV vaccines recently implemented in children's immunisation programs in many countries around the world are highly successful in helping to prevent RV infections (23). Both vaccines have been shown to be successful against commonly circulating genotypes of RVs including G1-4, G9, and P [4], P [6], and P [8] (25). However, as a result of the longterm use of such vaccines, possible vaccine escape strains could be selected in the future (44,45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two Rotarix ™ and RotaTeq ™ RV vaccines recently implemented in children's immunisation programs in many countries around the world are highly successful in helping to prevent RV infections (23). Both vaccines have been shown to be successful against commonly circulating genotypes of RVs including G1-4, G9, and P [4], P [6], and P [8] (25). However, as a result of the longterm use of such vaccines, possible vaccine escape strains could be selected in the future (44,45).…”
Section: Discussionmentioning
confidence: 99%
“…Rotaviruses in the family Reoviridae are icosahedral and triple layered viruses with eleven segmented double- stranded RNA (ds-RNA) genome ( 6 , 7 ). All eleven segments express six structural (VP1-VP4, VP6 and VP7) and six non-structural proteins (NSP1-NSP6) ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…These clusters also contained previously vaccine-derived strains isolated in Brazil, Korea, and Japan. Acute gastroenteritis, caused by vaccine shedding or horizontal transmissions of the vaccine strain have been reported at a higher rate in other countries [ 48 50 ]. Further analysis will be necessary to determine whether the observed vaccine strain was as a result of vaccine shedding or horizontal transmission event.…”
Section: Discussionmentioning
confidence: 99%
“…In Japan, where two live-attenuated oral rotavirus vaccines (Rotarix and RotaTeq) have been used voluntarily since 2011, analysis of 1824 stool samples from children at outpatient clinics with AGE identified the Rotarix vaccine-derived G1P[8] strain in 6 of 372 (1.6%) rotavirus-positive samples and no RotaTeq vaccine-derived strains 16. Wild-type rotavirus strains and other pathogens such as norovirus, Escherichia coli and enterovirus were also detected in two and four of the six samples, respectively, that were positive for the Rotarix vaccine-derived G1P[8] strain 16. The authors concluded that the contribution of the vaccine-derived strains to the children’s symptoms was unclear, although all six had been vaccinated 2–14 days before sample collection.…”
Section: Discussionmentioning
confidence: 99%